2006
DOI: 10.1177/0011000006288308
|View full text |Cite
|
Sign up to set email alerts
|

Treating Cronbach’s Alpha Reliability Coefficients as Data in Counseling Research

Abstract: Scientific associations and measurement experts in psychology and education have voiced various standards and best-practice recommendations concerning reliability data over the years. Yet in the counseling psychology literature, there is virtually no single-source compilation and articulation of good practices for reporting, analyzing, and interpreting reliability to guide applied researchers intending to use scales rather than develop them. Therefore, focusing on Cronbach’s alpha internal consistency reliabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
184
0
15

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(203 citation statements)
references
References 44 publications
4
184
0
15
Order By: Relevance
“…The overall content validity, face validity, construct validity and internal consistency reliability of the Persian version of the LMUP was supported based on the suggested criteria (11)(12)(13)(14)(15)(16). All the scale's items, with the exception of item 6 (preparation for pregnancy), met the item-to-total correlation criteria to be retained in the translated version.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The overall content validity, face validity, construct validity and internal consistency reliability of the Persian version of the LMUP was supported based on the suggested criteria (11)(12)(13)(14)(15)(16). All the scale's items, with the exception of item 6 (preparation for pregnancy), met the item-to-total correlation criteria to be retained in the translated version.…”
Section: Discussionmentioning
confidence: 93%
“…However, corrected item-to-total correlation index that represents whether an item in the scale is correlated with the remaining items was used to decide which items could provide meaningful information in explaining the proposed construct. Generally a minimum value of 0.4 is required for corrected item-tototal correlation index of an item to be kept in the scale (15).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding internal consistency, it was found that the Cronbach's alpha coefficients (α) values found for the subscale of parental support (α = 0.79) and for the friends' support (α = 0.90) were higher than the minimum value recommended (α greater than 0.70) to define acceptable internal consistency 25 . The same was observed for the values of the CFI.…”
Section: Rev Bras Epidemiol Apr-jun 2014; 355-370mentioning
confidence: 94%
“…The α values can be underestimated in scales with two or more factors 25 . The α and the CR values were considered satisfactory when equals or superior to 0.70 25 .…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, concurrent validity was indicated by significantly positive correlations with good academic adjustment (i.e., academic efficacy) for both the European and the Chinese American samples (see results of zero-order correlations in Table 3). Finally, although there is some disagreement regarding which level of internal consistency is considered acceptable (e.g., [43]), a reliability of .60 or above has been established as acceptable [44]. We averaged the item scores for each scale in this section for further analysis.…”
Section: Trainingmentioning
confidence: 99%